Characterization of the T Cell Response to Lactobacillus casei Cell Wall Extract in Children With Kawasaki Disease and Its Potential Role in Vascular Inflammation - Hsieh, Li-En; Tremoulet, Adriana H.; Burns, Jane C.; Noval Rivas, Magali; Arditi, Moshe; Franco, Alessandra (Frontiers in Pediatrics, 2021)
Lactobacillus casei cell wall extract (LCWE) induces in mice a vasculitis following intraperitoneal injection defined by the activation of macrophages, dendritic cells and CD8+ cytotoxic T cells leading to aortitis, coronary arteritis, aneurysms and myocarditis that strongly mimic the immunopathology and the cardiac lesions observed in children with Kawasaki disease (KD). KD is an acute febrile illness and systemic vasculitis of unknown etiology among young children, which can cause coronary artery abnormalities and aneurysms (CAA) and is the leading cause of acquired heart disease among children in the US. To address a potential pathogenic role of LCWE-specific T cells in human vascular inflammation, we studied the activation of circulating CD4+ and CD8+ T cells ex vivo in response to LCWE in three cohorts: 1) KD children 2-3 weeks after fever onset, 2) age-similar healthy children controls, 3) healthy adult controls. In all subjects studied, pro-inflammatory CD4+ and CD8+T cells responded to LCWE with no significant differences. Peripherally-induced regulatory T cells (iTreg) also responded to LCWE and potentially reverted to Th17, as suggested by the detection of IL-17 in culture supernatants. Central memory T cells were also detectable and were more abundant in adults. The potential homing to the vessels of LCWE-specific T cells was suggested by the expression of CCR6 and CD31. In conclusion, a non-pathogenic, LCWE-specific T cell repertoire could lead to KD depending upon priming conditions, genetic factors and immune activation by other antigens.